Perlindungan Hukum Kepemilikan Hak Atas Tanah Melalui Lembaga Rechtsverwerking - Kim Ahlam; Adonia Ivonne Laturette; Pieter Radjawane (PATTIMURA Law Study Review, 2026)
Disputes related to land continue to increase, resulting in numerous cases, one of which involves land ownership rights through the concept of rechtsverwerking (Waiver of Rights) for those who have already obtained land ownership certificates. Although this concept has been accommodated in legislation and in several Supreme Court jurisprudences, those who acquire land rights through this concept have not yet received legal protection in its application. This is due to differing perceptions among various parties, including the National Land Agency and the judiciary, with some believing that applying this concept could undermine the rights of landowners. This issue has drawn the author’s attention for further examination in this thesis. The research methodology employed in this thesis is normative juridical research with a descriptive-analytical approach to legislation. The study utilizes primary, secondary, and tertiary legal sources through a procedure for gathering and analyzing legal materials to draw conclusions. The research findings indicate that the principle of good faith in land ownership through the concept of rechtsverwerking can be applied to land possession by a party who has held the land openly and in good faith for an extended period. Such possession allows the party to register the land to obtain a property certificate after more than five years since issuance. In this case, the previous owner cannot object or reclaim their rights, as, based on the concept of rechtsverwerking, they are considered to have waived or relinquished their rights, thus resulting in the loss or cancellation of their rights. Therefore, land ownership through the rechtsverwerking concept should receive legal protection. Legal protection for land ownership rights based on the rechtsverwerking concept is closely linked to the issue of justice in legal implementation. Protection for land rights holders under rechtsverwerking consists of preventive and repressive measures. Therefore, the government, specifically the relevant institutions, should conduct socialization regarding the application of the rechtsverwerking concept in obtaining land ownership rights.